Exploring the diversity of biological processes regulated by glial cell line-derived neurotrophic factor, a pleiotropic molecule with therapeutic potential - Porcari, Cristina; Cattaneo, Stefano; Crippa, Lucia; Simonato, Michele; Bettegazzi, Barbara (Frontiers in Physiology, 2025)
Glial cell line–derived neurotrophic factor (GDNF) is a potent trophic factor essential for neuronal survival and function. Encoded by the GDNF gene, its mature protein arises from specific post-translational modifications and is secreted through distinct isoform-dependent pathways. Once released, GDNF binds to its receptors, GFRα1 and RET, activating downstream signaling cascades that regulate cell growth, differentiation, and survival. In the central nervous system, GDNF exerts protective effects on dopaminergic neurons—highlighted in Parkinson’s disease research—and shows promise for modulating schizophrenia, depression, and addiction. Beyond dopaminergic pathways, GDNF influences synaptic plasticity in hippocampal neurons and supports GABAergic function. Glial cells also produce and respond to GDNF: astrocyte-derived GDNF can promote neuroprotection but also modulate microglial state and neuroinflammation. Other cell sources, such as pericytes and endothelial cells, contribute to GDNF levels, impacting blood-brain and blood-nerve barrier permeability. Peripherally, GDNF is critical for sympathetic and parasympathetic neuron development, somatic sensory neuron maintenance, and motor neuron reinnervation at the neuromuscular junction. Finally, GDNF has been recently implicated in tumour biology, underscoring its multifaceted role at the interface between beneficial and detrimental effects. Clinically, its therapeutic potential is being explored in different diseases, including neurodegenerative disorders and epilepsy. In this review, we will explore various aspects of GDNF biology and then focus our attention to the physiological mechanisms of GDNF-regulated processes in the central and peripheral nervous system, concluding with a brief perspective related to its therapeutic potential for central nervous system disorders. A deeper knowledge of the mechanisms regulating GDNF secretion and signaling, particularly the cellular source and the specificity of the GDNF-engaged intracellular signaling pathways, could be helpful to develop more precise therapeutic strategies for different CNS diseases.